Interstitial 14q31.3-q32.13 deletion : the role of molecular karyotyping in clarifying the etiology of developmental delay - Crkvenac Gornik, Kristina (Array, 2019)
Aim: With the exception of ring chromosome 14 or translocations, interstitial deletions of the long arm of chromosome 14 are very rare. All patients with these deletions share common phenotypic characteristics, primarily mild dysmorphia and developmental delay. Molecular karyotyping (array CGH) enabled the precise breakpoint determination and improved the analysis of genotype-phenotype correlations. Case presentation: In a 7-year-old girl, array CGH was performed due to developmental delay. The array CGH study showed 8.3Mb de novo interstitial deletion of the 14q31.3–q32.13 region. Conclusions: Comparison of our patient´s phenotype with previously reported chromosome 14q interstitial deletion cases confirmed the presence of common clinical features and highlights the utility of array CGH as a diagnostic tool in clarifying the developmental delay etiology.